Sea and Ocean as Fountains of Islanders’ Life and Creative Activities: An Ecological Perspective to Confront the Global Crisis - Konishi, Junko (UPT Pusat Penerbitan LP2MPP ISI Bali, 2023)
This paper considers the possibility of arts and performing arts to challenge the global crisis of the so called Anthropocene. It is the most recent period in Earth’s history when human activities significantly impacted the climate and ecosystems. This is exemplified by the case of Miyako Islands, the remote islands of Okinawa Prefecture, which illustrate how water has been fountains of islanders’ lives and creative activities is discussed. The theoretical background of this study includes nissology (island study) that has established the concept of an island,